Preparation and characterization of Ce0.85La0.15 − xSrxO{2 − (0.075 + x / 2)} solid electrolytes for intermediate temperature solid oxide fuel cells - Jaiswal N.; Kumar D.; Upadhyay S.; Parkash O. (My University, 2025)
A few compositions in the system Ce0.85La0.15 − xSrxO{2 − (0.075 + x / 2)} have been prepared using citrate-nitrate method. More than 95 % of theoretical density has been obtained by sintering at 1,350 °C for 4 h in air. Solid solution forms in all the compositions. Surface morphology has been studied by scanning electron microscope (SEM). Morphology of powder has been studied by bright field transmission electron microscopy (BFTEM). Complex plane impedance measurements have been made in the frequency range 1 Hz–1 MHz between 200 and 600 °C to separate the contributions of grains, grain boundaries, and electrode-specimen interface polarizations. Composition, Ce0.85La0.125Sr0.025O1.9125, exhibits the maximum conductivity 1.50 × 10−2 S/cm at 600 °C which is much higher than that of ceria doped with La only in the intermediate temperature range. Co-doping with Sr increases the bulk as well as grain boundary conductivity. © 2014, The Author(s).